Impact of short-term (24 h) blood pressure variability on 30-days clinical outcomes of acute strokes at two tertiary hospitals in Dar-es-Salaam - Mashambo, Ayubu Eliesikia; Makakala, Mandela Charles; Adebayo, Philip Babatunde (Frontiers in Stroke, 2025)
BackgroundStroke remains the second leading cause of disability and death worldwide, with hypertension as its principal risk factor. Evidence from high-income countries indicates that blood pressure variability (BPV) is an independent predictor of outcomes during the acute phase, but data from African populations are limited despite the rising burden of cardiovascular disease. Understanding BPV patterns in this context is crucial for designing interventions to improve stroke outcomes.ObjectivesTo determine 24-h BPV patterns in acute stroke patients and assess their impact on 30-day functional outcomes.MethodsThis multicenter prospective cohort study enrolled adults with acute stroke presenting within 72 h of symptom onset at two tertiary hospitals in Dar es Salaam. BPV patterns were measured using 24-h ambulatory monitoring, and demographic, clinical, and stroke subtype data were collected. Functional outcomes were evaluated using the modified Rankin Scale (mRS) and Barthel Index at admission, day 7, and day 30. Associations were examined using logistic regression.ResultsOf 52 patients enrolled, 48 (92.3%) completed follow-up. Most were male (n = 31; 64.6%), middle-aged (47–60 years, n = 19; 39.6%), and hypertensive (n = 43; 91.5%). Hemorrhagic strokes (n = 27; 56.3%) demonstrated higher systolic and diastolic BP variability than ischemic strokes, though differences were not statistically significant. Impaired nocturnal dipping (day/night systolic BP ratio) was linked to poor outcomes in univariate analysis (p = 0.019) but lost significance in multivariate testing (p = 0.16). Functional outcomes improved significantly by day 30: the Barthel Index increased, and mRS scores decreased. NIHSS score at day 7 emerged as the strongest independent predictor of poor outcome (mRS: p = 0.027, OR = 3.04, 95% CI: 1.13–8.15). Higher education level was also associated with better functional outcomes (p = 0.03).ConclusionIn this Tanzanian cohort, reduced nocturnal dipping and elevated morning pressures were the most frequent BPV patterns, especially in hemorrhagic strokes, though not independently associated with outcomes at 30 days. Neurological severity at day 7 (NIHSS) was the strongest predictor of recovery, and lower education levels negatively influenced outcomes. The Barthel Index was more sensitive than the mRS in detecting functional gains.